Career Counseling for International Students: Using the Framework of Social Cognitive Career Theory - 2020 (chapter 51) - Bulgan, Gökçe; Çiftçi, Ayşe (IGI Global, 2020)
International students are a group with diverse career needs and concerns. The challenges international students face (e.g., psychological and sociocultural adjustment issues, language barriers, sense of loss, financial problems, getting used to a new educational system) when they come to study in the United States, as well as their expectations of coming to a new country, may significantly influence their career needs and decision-making processes. In this chapter, the authors suggest social cognitive career theory (SCCT) as a framework for working with the undergraduate and graduate international student population by emphasizing intervention strategies and making specific recommendations. © 2021 by IGI Global. All rights reserved.
Keywords: Sociat cognitive career theory